Pengembangan Model Publikasi Karya Ilmiah Berbasis Teknologi Informasi pada Mahasiswa Pendidikan Agama Islam - St. Wardah Hanafie Das; Asran Asran; Sutriana Sutriana; Sudarmin Sudarmin; Darmawati Taro (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Publication of scientific papers is an important indicator in the development of academic culture in higher education, including in the Islamic Religious Education (PAI) study program. However, PAI students still face various obstacles in publishing scientific papers, such as limited understanding of the publication system, low information technology literacy, and minimal structured mentoring. This study aims to develop an effective and applicable information technology-based scientific paper publication model for PAI students. This study uses a research and development approach by adapting the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were students of the Islamic Religious Education Study Program at an Islamic religious college. Data collection techniques included observation, interviews, questionnaires, and documentation studies. The results of the study indicate that the information technology-based scientific paper publication model developed consists of five main components, namely (1) scientific writing training based on the Learning Management System (LMS), (2) the use of digital reference management applications, (3) the use of online journal platforms and institutional repositories, (4) publication assistance through collaborative media, and (5) digital-based evaluation and feedback. Implementation of this model has been proven to improve students' understanding of the scientific publication process, their skills in using information technology, and their motivation to publish scientific papers. Therefore, this model is suitable as an alternative strategy for strengthening Islamic Religious Education students' scientific publications in the digital era.